Domestic violence against children and adolescents in Taif, Saudi Arabia: Analytical study from the school counsellor’s perspective - Al Hariri, Ahmed; Faisal, Eman; Al Harthi, Rasha; Al Harthi, Fozeah; Al Harthi, Amal Hamed (European Scientific Journal, ESJ, 2021)
The study aimed to recognise the differences, relationships, and prediction of domestic violence among school students from the school counsellors in Taif, Saudi Arabia. A mixed-methods approach was used in collecting and analysing quantitative and qualitative data. A questionnaire and interviews were used. The sample that answered the questionnaire included 84 schools’ counsellors, whereas the sample that answered the interviews was 13 schools’ counsellors. Results showed that there are significant differences at p < .05 in the domestic violence suffered by students: students in primary school (M = 3.83; SD = .910), and in particular the students who study in schools with between 1001 and 1200 students (M = 2.301; SD = .311) and who study in schools with between 801 and 1000 (M = 2.299, SD = .419), but there was no difference regarding the experience of schools’ counsellors. There were positive correlations at p < .05 between domestic violence and both the total number of students in a school (rho = .14) and the experience of schools’ counsellors (rho = .09) but not with the stage of education. It is also impossible to predict domestic violence incidents by using the total number of students in a school, schools’ counsellors’ experience, and the stage of education. Qualitative data from the interviews were used to support the findings of the quantitative data. For example, school counsellors from secondary school stressed that they dealt with students who suffer from domestic violence, and from crowded schools agreed that they saw many students who suffer from domestic violence. The results of this article showed the importance of investigating domestic violence in under-researched societies, such as school students from Saudi Arabia. This study ended with some recommendations. One recommendation is to have enough schools’ counsellors based on the total number of students in a school. Other recommendations that enhance mental health in schools and increase the quality of a schools’ counsellor’s work.